A Method for Preparing Manganese-Doped V2O5 Films with Enhanced Cycling Stability. Issue 7 (1st January 2016) - Guan, Shian; Wei, Youxiu; Zhou, Junling; Zheng, Jianming; Xu, Chunye
Abstract : An efficient new method was investigated for preparing smooth manganese (Mn) doped V2 O5 films. This method uses cathodic electrodeposition to dope Mn ions into V2 O5 films. The doped Mn concentration was in proportion to the applied voltage. X-ray diffraction patterns and Raman spectra were measured to detect the structure change of V2 O5 . The influence of Mn concentration on morphology, electrical, and optical properties of the films were also studied. Repeated chronocoulometry was applied to investigate the cycling stability of films with different Mn concentration. The results showed that the charge capacity of Mn-doped film was more stable than pure V2 O5 film during cycling process. Moreover, the method will be useful in doping various ions into V2 O5 .